2014
DOI: 10.1186/2008-6695-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element studies on free vibration of cylindrical skew panels

Abstract: An effective form-finding method for form-fixed spatial network structures is presented in this paper. The adaptive formfinding method is introduced along with the example of designing an ellipsoidal network dome with bar length variations being as small as possible. A typical spherical geodesic network is selected as an initial state, having bar lengths in a limit group number. Next, this network is transformed into the ellipsoidal shape as desired by applying compressions on bars according to the bar length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Also the natural frequencies increase with an increase in the skew angle. These findings are in excellent agreement with Srinivasa et al [30].…”
Section: Anti-symmetric Skew Laminatessupporting
confidence: 93%
“…Also the natural frequencies increase with an increase in the skew angle. These findings are in excellent agreement with Srinivasa et al [30].…”
Section: Anti-symmetric Skew Laminatessupporting
confidence: 93%
“…Lanczos method was used in the present study as it combines the best features of the other methods and computes accurate eigenvalues and eigenvectors [22,26]. Table 2 shows the results of validation.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…The CQUAD8 element is a eight-node isoparametric shell element having six degrees of freedom / node (translational (u, v, w) and rotational (θx, θy, θz)). Both the elements take into account the shear deformations [20][21][22][23][24][25][26].…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…But the analysis of stiffened shells with cutout for higher modes is scanty in the literature. Some studies [24,25] also reported the mode frequency analysis of laminated spherical and cylindrical shells. However, the analysis of stiffened hypar shells with cutout for higher modes is yet to be reported in literature.…”
Section: Introductionmentioning
confidence: 99%